PENERAPAN ALGORITMA GENETIKA PADA METODE WINTERS UNTUK PERAMALAN NILAI TUKAR MATA UANG - Andry Pratama Chiarli; Helmy Thendean (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The appliance of Genetic Algorithm with Winters Method for currency exchange value prediction is an application which purpose is to predict currency exchange value in the next one timeline. The objective of the research is to create a prediction application for predicting the exchange value of Rupiah by using US Dollar as a comparison variable and Genetic Algorithm to find optimal parameter values which are used in Winters Method. The Winters Method is a method used for exponential interpolation which is usually called Three Exponential Interpolation Method that considers changes of seasons and trends. One of the problems that encountered in Winters Method application is finding the parameter values, which are  and . To find the solution for previous problem, then Genetic Algorithm is used to find the parameter values in order to perform optimization on Winters Method. The input uses actual data, then prediction is performed on the data by using Winters Method. The output is prediction value for the next period. The accuracy resulted from testing the exchange value between US Dollar to Rupiah is 99,81%.